2019
DOI: 10.1111/asap.12181
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Narratives: Predictors of Jewish American and Arab American Support for a Two‐State Solution to the Israeli–Palestinian Conflict

Abstract: In a survey study of Arab and Jewish Americans, we examined which beliefs best predicted support for a two-state solution. We compared the role of a sense of collective victimhood, dehumanization of the outgroup, a zero-sum view, and a monolithic narrative on the conflict. In both the Arab American and the Jewish American samples, framing the conflict in terms of a monolithic narrative played the strongest role in predicting rejection of a two-state solution. On the other hand, when Jewish Americans agreed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Research on political conflict and conflict resolution has demonstrated that narratives are particularly critical in understanding political conflict. The psychological construct of a narrative has been integral in understanding why individuals support the perpetuation of conflict (Bar-Tal et al, 2014;Ben Hagai & Zurbriggen, 2019;Klar & Baram, 2016;Oren et al, 2015;Rotberg, 2006). For instance, several studies indicate that the narrative that depicts Jewish Israelis as having a strong connection to the land or as wishing to live in peace but must defend themselves clashes with narrative that depict the Palestinians as indigenous to the land but as dispossessed and oppressed by Israel (Ben Hagai, et al, 2013, 2013b.…”
Section: The Clashing Narrative Approach To Political Conflictmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on political conflict and conflict resolution has demonstrated that narratives are particularly critical in understanding political conflict. The psychological construct of a narrative has been integral in understanding why individuals support the perpetuation of conflict (Bar-Tal et al, 2014;Ben Hagai & Zurbriggen, 2019;Klar & Baram, 2016;Oren et al, 2015;Rotberg, 2006). For instance, several studies indicate that the narrative that depicts Jewish Israelis as having a strong connection to the land or as wishing to live in peace but must defend themselves clashes with narrative that depict the Palestinians as indigenous to the land but as dispossessed and oppressed by Israel (Ben Hagai, et al, 2013, 2013b.…”
Section: The Clashing Narrative Approach To Political Conflictmentioning
confidence: 99%
“…In this research, we use a clashing narrative framework to understand political conflict in the United States (Ben Hagai & Zurbriggen, 2019). We propose that above and beyond, ideological dispossessions identified to predict political choices, in the United States two master narratives that of the American dream and another the United States as a systematic racist country explain individuals’ political choices.…”
Section: Introductionmentioning
confidence: 99%
“…Survey studies of Jewish and Arab Americans show a similar pattern of beliefs: Jewish Americans tend to agree with the root narrative in which Jewish Israelis want to live in peace but have to defend themselves, whereas Arab Americans tend to agree with the root narrative that frames the Palestinians as indigenous to the land but as dispossessed and suffering. When Jewish Americans or Arab Americans agreed with their own collective narrative and disagreed with the narrative of the other, they were more likely to reject peaceful solutions to the Israeli–Palestinian conflict (Ben Hagai, 2017).…”
Section: Beliefs Common Among Groups In Conflictmentioning
confidence: 99%